2011
DOI: 10.1029/2010ja016249
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen ion precipitation in the Martian atmosphere and its relation with the crustal magnetic fields

Abstract: [1] Without a global intrinsic magnetic field, oxygen ions in the Martian atmospheric corona can be picked up by the solar wind directly. The majority of the pickup ions escape, while some can precipitate into the atmosphere, producing sputtering of atmospheric constituents, which may play a significant role in the loss of neutral atmosphere. With its widely distributed crustal magnetic fields, Mars is unique. While it has been shown that Mars's crustal fields can alter the global distribution of escaping ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 26 publications
4
23
1
Order By: Relevance
“…The observed precipitating flux is also at the same order of magnitude as the predictions of Li et al []. These are consistent with the predictions by Chaufray et al [] and Li et al []. Our obtained feature in terms of the precipitating location in the MSE coordinate system shown in Figure might also support such previous numerical predictions.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The observed precipitating flux is also at the same order of magnitude as the predictions of Li et al []. These are consistent with the predictions by Chaufray et al [] and Li et al []. Our obtained feature in terms of the precipitating location in the MSE coordinate system shown in Figure might also support such previous numerical predictions.…”
Section: Discussionsupporting
confidence: 93%
“…In our observation, the precipitating PHIs are frequently observed at the low‐SZA region (Figure b). The observed precipitating flux is also at the same order of magnitude as the predictions of Li et al []. These are consistent with the predictions by Chaufray et al [] and Li et al [].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Recent studies that included enhanced solar wind, such as the passing of interplanetary coronal mass ejections (ICMEs), solar energetic particle event, or corotating interaction regions (CIRs), suggested that the sputtering effects may significantly increase for short periods due to vary large transient ion precipitation fluxes and energies [ Leblanc et al , ; Hara et al , ; Wang et al , ]. On the other hand, the existence of the surface crustal fields and their various interactions with the IMF can affect the pickup ion escape rates and the precipitation energy and fluxes as well as the resulting sputtering efficiencies [ Ma et al , ; Ma and Nagy , ; Fang et al , ; Li et al , ]. Therefore, an overview of sputtering effects covering a range of Mars environments and related interaction with the solar wind should be studied in more detail to get better estimates of the variability of these effects and their influence on Martian atmosphere evolution.…”
Section: Introductionmentioning
confidence: 99%